Implementasi Program Kawasan Tanpa Rokok di Stasiun Poncol Kota Semarang - Egy Bramantya Akbar; Hartuti Purnaweni; Aloysius Rengga (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Health is a major factor for a nation in order to carry out the construction. Air is essential for life, as a natural resource that is vital for life, then the decrease in air quality is very influential for the survival of humans and other living beings, so that air quality must be maintained. To protect air quality control measures against sources of air pollutants and to activities that have the potential to pollute the air, such as smoking. One of the efforts made by the government through the Ministry of Health of the Republic of Indonesia is a program No-Smoking Area. No-Smoking Area program is a program that is set up where only place allowed to smoke, such as public places and transport, etc. Through this program, the central government provide a smoke-free policies to places that become Smoking Area. This research was conducted in Poncol Station Semarang City which is one of the crowded station in Semarang. The research was based on the fact that in its implementation, still there are problems such as the persistence of the violation of the public who smoke in any place. The aim of this study is to describe and analyze how the implementation Smoking Area Program in Semarang and describe the supporting factors and obstacles in the implementation of programs Smoking Area in Poncol Station Semarang. Based on research, program implementation Smoking Area in Poncol Station Semarang is still not optimal. Therefore, the recommendations can be given is to improve the smoking area to create a smoking room, so the smoke of the active smokers do not get out of the room that has been provided and the utilization Smoking Area program can be more optimally.